Implementasi Sistem Kendali Kecepatan Kursi Roda Elektrik Menggunakan Kendali Proporsional Pada Kondisi Jalan Menanjak Dan Menurun - Achmad Fanani Kurniawan Saputra; Dahnial Syauqy; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Health is one of important thing, because an awful lot of diseases that can causing difficulties when moving, so we need tools like a wheelchair. wheelchairs have an awful lot of development, one of which namely electric wheelchairs. The application of electric wheelchair still not have a feature to adjust the speed while on the uphill and downhill road conditions so that safety and comfort will be reduced. Speed control system using proportional control while on the condition of the streets uphill and downhill works by checking the condition of the slope sensor path with GY-521 MPU6050 whose value will be used as the parameters change speed maximum. the speed read by the Encoder FC-03 was calculated using proportional control which will produce output to set the speed of the motor and will always check if it's value has reached set point is expected. on the uphill road conditions the system will add speed to the value of RPM can match the set point, whereas at the moment the road conditions decreased system will lower the speed so the RPM value can be fixed in accordance with the set point. The testing results of this system show the percentage success system when uphill road condition of 78.5% and when downhill road condition is 85.61%.